(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This study was conducted to determine the influence of Principals’ administrative strategies on school plant maintenance in secondary schools in Taraba State, Nigeria. The study was guided by four objectives and four research questions were answered, while four null hypotheses were formulated and tested at 0.05 level of significance. Survey research design was used and the population of the study was 618 Principals and vice principals from all the 309 public secondary schools in the Taraba State. The study was a census survey of the entire population hence there was no sampling. A 41-items self- structured questionnaire titled “Influence of Principals’ Administrative Strategies on School Plant Maintenance Questionnaire “IPASSPMQ” was used to collect data from the respondents. Five Experts made up of three experts from Educational Administration and Planning; two experts in and Measurement and Evaluation in the Department of Educational Foundations and General Studies, Joseph Sarwuan Tarka University, Makurdi ensured the face and content validity of the instrument. The IPASSPMQ was trial tested on respondents in five secondary schools in Benue state and the reliability of the instrument was also established using Cronbach Alpha formula which yielded an index of 0.83. The data collected were analysed using Frequency count, Mean and Standard Deviation to answer research questions while hypotheses were tested using Chi-square goodness of -fit- statistical tool at 0.05 level of significance. The study found that all the principals’ administrative strategies of planning, organizing, staffing and coordinating has significant positive influence on school plant maintenance in secondary schools in Taraba state. It was recommended amongst others that Principals and Vice principals of secondary schools in Taraba state should provide active and efficient coordination of all their school plant activities with the aim of aim of sustaining the smooth operation of the school plant.